2001
DOI: 10.1074/jbc.m007304200
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Incorporation of Nascent Molybdenum Cofactor into Human Sulfite Oxidase

Abstract: We were able to reconstitute molybdopterin (MPT)-free sulfite oxidase in vitro with the molybdenum cofactor (Moco) synthesized de novo from precursor Z and molybdate. MPT-free human sulfite oxidase apoprotein was obtained by heterologous expression in an Escherichia coli mutant with a defect in the early steps of MPT biosynthesis. In vitro reconstitution of the purified apoprotein was achieved using an incubation mixture containing purified precursor Z, purified MPT synthase, and sodium molybdate. In vitro syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 21 publications
2
48
0
1
Order By: Relevance
“…A control experiment using bovine serum albumin instead of XDH showed that Moco insertion was specific to apo-XDH (data not shown). This reconstitution efficiency is less than the in vitro insertion of Moco described for hSO, where about 50% could be achieved (20). However, since XDH displays a 2.5 times higher molecular mass (275 kDa) than hSO (ϳ110 kDa), the lower levels of in vitro Moco reconstitution might be due to the complexity of the XDH structure and to a less stable conformation of the Moco-free apo-XDH.…”
Section: Analysis Of the Ability Of Xdhc To Insert Moco Intomentioning
confidence: 72%
“…A control experiment using bovine serum albumin instead of XDH showed that Moco insertion was specific to apo-XDH (data not shown). This reconstitution efficiency is less than the in vitro insertion of Moco described for hSO, where about 50% could be achieved (20). However, since XDH displays a 2.5 times higher molecular mass (275 kDa) than hSO (ϳ110 kDa), the lower levels of in vitro Moco reconstitution might be due to the complexity of the XDH structure and to a less stable conformation of the Moco-free apo-XDH.…”
Section: Analysis Of the Ability Of Xdhc To Insert Moco Intomentioning
confidence: 72%
“…The MPT-Mo cofactor can either be inserted into MPT-free apoenzymes or undergo subsequent addition of a nucleotide, for example GMP in E. coli by the MobA protein. However, in vitro reconstitution studies of MPT-enzymes such as sulfite oxidase have indicated that conversion of MPT to active Moco by molybdate chelation and its subsequent incorporation can be performed in the absence of MogA and MoeA (13). Similar studies performed on MGDenzymes such as Me 2 SO reductase from Rhodobacter sphaeroides have shown that both MobB and a chaperone protein are not absolutely required for MGD insertion (15).…”
mentioning
confidence: 67%
“…The crystal structure of most of the proteins involved in the biosynthetic pathway of Moco have been determined recently (4 -12). Biochemical studies have indicated that newly formed MPT remains tightly bound to the MoaD-MoaE complex (MPT synthase) until its transfer to proteins able to bind it with higher affinity (13). MogA and MoeA proteins constitute such candidates and have been shown to bind MPT with distinct affinities (6,11,14).…”
mentioning
confidence: 99%
“…Since tight binding of MPT to MoaE had been observed previously (9,28) (MoaE-MoaD-SH) were passed through a desalting column equilibrated in water and concentrated prior to negative ion mass spectroscopy.…”
Section: Resultsmentioning
confidence: 99%